COMPARATIVE ANALYSIS OF THE COMPANY'S FINANCIAL PERFORMANCE BEFORE AND AFTER CONDUCTINGSPIN-OFF AT PT. MITRA ADIPERKASA TBK. - JULIA KARINA; MUHAMMAD FAUZAN (Indragiri Research Center (ingreat), 2023)
This study aims to determine differences in financial performance at PT. Mitra Adiperkasa Tbk. before and after spin-off. Sampling using saturated sampling technique (census), the sample in this study is the company's quarterly financial reports for 5 years before the spin-off and 5 years after the spin-off as many as 40 quarterly financial reports. Methods of data collection using documentation study methods, literature studies and web searching. The analysis technique used is descriptive statistics, normality test and hypothesis testing using paired sample t-test. The results showed that based on the CR (Current Ratio) variable, there were differences in the financial performance of PT. Mitra Adiperkasa Tbk before and after the spin-off. Meanwhile, the ROA (Return On Assets), DAR (Debt to Asset Ratio) and TATO (Total Asset Turnover) variables show that there is no difference in the financial performance of PT. Mitra Adiperkasa Tbk before and after the spin-off.